Influence of storage times on bond strength of resin cements to root canal - Bandéca, Matheus Coêlho [UNESP]; Kassem, Amr Shebl; El-Mowafy, Omar; Nadalin, Michele Regina; Queiroz, Renato Souza [UNESP]; Clavijo, Victor Rene Grover [UNESP]; Saad, José Roberto Cury [UNESP] (Universidade Federal de São Carlos (UFSCar), Dept Engenharia Materials, 2010)
The resin cements are responsible to retention of the indirect materials decreasing marginal leakage, increasing failure resistance compared with conventional cementation. The cementation within root canal is very hard due unfavorable conditions regarding the application of adhesive techniques caused by inadequate access. Therefore, considering the possibility to decrease steps of cementation, this study was performed to evaluate the bond strength of self-adhesive resin cement (RelyX (TM) U100, 3M ESPE) and resin cement combined with self-ecthing adhesive system (Panavia (R) F 2.0, Kuraray) light-cured with Quartz Tungsten Halogen (QTH) following storage at 37 degrees C immediately after light-curing, 24 and 48 hours and 7 days. The root canals were prepared to receive the glass fiber post in the depth of 10 mm, irrigated with 17% EDTA and NaOCl, rinsed with distilled water and dried using paper points. The roots were perpendicularly sectioned into approximately 1 mm thick sections, obtaining ninety-six slices (n = 12). The slices were trimmed using a cylindrical diamond bur in the proximal surfaces until it touched the post and attached into a device, which were mounted on a strength tester (Bisco) and loaded in tension at a speed of 0.5 mm/min until failure occurred at specimens. The analysis of variance (ANOVA) and Tukey's post-hoc tests showed significant statistical differences (P < .05) to all resin cements immediately after light-curing and 24 hours, 48 hours and 7 days. The Panavia (R) F 2.0 showed higher mean values than RelyX (TM) U100 for all storage times, however no different statistically significant was reported (P > .05). The resin cements 24 and 48 hours after light-curing were statistically similar among themselves (P > .05). The both resin cement showed similar bond strength into root canal on different storage times. The highest bond strength values of the resin cements were showed 7 days after curing.
Keywords: Adhesion; Dental polymers; Light curing; Polymerization; Adhesive systems; Bond strength; Distilled water; Failure resistances; Infuence; Kuraray; Mean values; Quartz tungsten halogen; Resin cement; Root canals; Self-adhesive; Statistical differences; Bond strength (materials); Canals; Cementing (shafts); Curing; Hydraulic structures; Oxide minerals; Polymers; Quartz; Regression analysis; Resins; Statistical tests; Tungsten; Cements